Current Practices of Corrective Feedback in Indonesian Secondary EFL Classrooms: A Systematic Review - Maslucha, Saniatul; Firmansyah, Muhammad Alvin; Uswah, Maulidiyyatul; Rachmatian, Noor Apriyan (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
In the dynamic landscape of English as a Foreign Language (EFL) education in Indonesian secondary schools, the significance of corrective feedback emerges as a focal point for enhancing language development, refining writing abilities, and shaping students' attitudes. the paper incorporates an examination of students' responses and attitudes towards corrective feedback, providing valuable insights into the effectiveness and reception of these strategies. Through a comprehensive literature review, the article aims to contribute to the ongoing discourse surrounding the implementation of corrective feedback in Indonesian EFL education, offering a nuanced understanding of both teacher practices and student perspectives. The investigation meticulously scrutinizes both written corrective feedback (WCF) and oral corrective feedback, shedding light on the myriad strategies employed by educators and the diverse responses emanating from students across different educational tiers. Additionally, the research delves into students' responses and attitudes towards corrective feedback across different school levels, revealing varying reactions.